The role of biodegradable nonwoven fabrics in efficient sodding of earth structures - Piotr Kacorzyk; Katarzyna Starzec; Paweł Kaszycki; Paulina Supel (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Newly formed earth structures such as ski slopes are areas causing difficulties in attempts for efficient sodding since colonization with plants, where initial development and adaptation are hindered due to unfavourable climatic and soil factors. The main objective of the study was to demonstrate the feasibility of using nonwoven fabrics made from sheep’s wool and waste poultry feathers on steep-gradient mountain slopes.